Association between hearing loss and vestibular disorders : a review of the interference of hearing in the balance - Santos, Tatiana Guthierre Targino dos (2015)
Dizziness is very prevalent and makes a great impact on people’s life. Because of anatomical and functional similarities of hearing and vestibular systems, it is noted that there is a big relation between hearing loss and vestibular disorders. Depending on the age onset of hearing loss, it can cause even delay on motor development. Objective: To find literature that demonstrates the relation between hearing and balance. Confirming that hearing loss or even intervention to improve quality of hearing can interfere on vestibular system. Methodology: Revision of literature was carried out, preferring recent research only in English. Conclusion: Cochlea and vestibular systems have a close relationship; changes in one of them can cause big damage in the other. So, a complete evaluation of vestibular system is recommended before ear surgeries. Video Head Impulse Test is a new procedure able to evaluate high frequency movements of the head. It was an additional exam of vestibular status and came to help detect problems that were not diagnosed before. Efforts must be directed in order to protect the balance.